Solving unit commitment problem with solar photovoltaic and wind energy generation by using multi-agent evolutionary programming technique / Putri Azimah Salleh - Salleh, Putri Azimah (2014)
The goal through this paper is to solve unit commitment problem in power system with solar and wind energy generation. This approach objective to find optimal solution using Multi Agent Evolutionary Programming technique to minimize cost when implementing renewable energy and review the effect of solar and wind energy to unit commitment. The conventional unit commitment consists of schedule of start-up cost and shut-down generating unit that meet the demand of power generation. Several Artificial Intelligence (AI) techniques such as Multi Agent and Evolutionary Programming were combine to produce Multi Agent Evolutionary Programming (MAEP) technique. There are 10 generator units with 24 hours periods and a few constraints considered in this study such as generator limit, load demand, spinning reserve margin and hot start-up cost. The combination MAEP algorithm includes mutation process, combination and selection the least cost. It is expected that by implementing MAEP with solar and wind, the cost of operation is optimized rather than without renewable energy conventional Evolutionary Programming technique.